Rapid development of severe acute respiratory distress syndrome after abatacept treatment in a patient with rheumatoid arthritis. Issue 4 (6th April 2020) - Gower, Jorge; Labarca, Gonzalo; Enos, Daniel; Nova-Lamperti, Estefania
Abstract : Abatacept is a biological agent that modulates T-cell costimulation by blocking CD28 signalling. This cytotoxic T-lymphocyte-associated antigen-4-Ig fusion protein was approved for treatment of rheumatoid arthritis (RA). However, a few case reports have revealed respiratory failure after abatacept treatment. In this report, we present a patient with RA who developed severe acute respiratory distress syndrome (ARDS) and who passed away 2 months after starting abatacept. A comprehensive analysis including radiology, blood examinations, infectious panel and flow cytometry lymphocyte analysis was done to determine the cause of respiratory failure. Since no infection was detected in this patient, an association between ARDS and abatacept is a strong possibility due to significant adverse reactions to the biological agent. Considering the rapid progression of respiratory failure after abatacept treatment in this report, we suggest that pulmonary function testing and lung structure evaluation be regarded throughout the early stage of treatment of patients with RA.